2017
DOI: 10.3748/wjg.v23.i32.5977
|View full text |Cite
|
Sign up to set email alerts
|

New botanical drug, HL tablet, reduces hepatic fat as measured by magnetic resonance spectroscopy in patients with nonalcoholic fatty liver disease: A placebo-controlled, randomized, phase II trial

Abstract: AIMTo evaluate the efficacy and safety of HL tablet extracted from magnolia officinalis for treating patients with nonalcoholic fatty liver disease (NAFLD).METHODSSeventy-four patients with NAFLD diagnosed by ultrasonography were randomly assigned to 3 groups given high dose (400 mg) HL tablet, low dose (133.4 mg) HL tablet and placebo, respectively, daily for 12 wk. The primary endpoint was post-treatment change of hepatic fat content (HFC) measured by magnetic resonance spectroscopy. Secondary endpoints incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(38 reference statements)
0
11
0
Order By: Relevance
“… IM T: 1–12 years C: 1–13 year 140 (70, 70) 83, 57 T: 42.9 ± 5.3 C: 43.2 ± 5.7 8 Jiang et al, 2017 [ 41 ] Dahuang Lidan capsule Rhei Radix Et Rhizoma, Phyllanthi Fructus and Radix Gymnadeniae IM N/A 144 (72, 72) 104, 40 T: 43.0 ± 0.03 C: 43.4 ± 7.60 9 Yang et al, 2017 [ 53 ] Cigu Xiaozhi capsule Cremastrae Pseudobulbus, Alismatis Rhizoma, Crataegi Fructus, Salviae Miltiorrhizae Radix Et Rhizoma, Radix Bupleuri, Pinelliae Rhizoma Praeparatum, Cassiae Semen, etc. WM N/A 87 (43, 44) 50, 37 T: 49.02 ± 11.19 C: 50.63 ± 10.97 10 Jeong et al, 2017 [ 28 ] HL tablet Extract of Magnolia officinalis WM N/A 72 (22, 23, 23)* 54, 18 H: 39.1 ± 9.5 L: 45.5 ± 11.5 C: 42.7 ± 11.2 11 Sun et al, 2017 [ 68 ] Jianpi Qushi prescription Codonopsis Radix, Poria, Microctis Folium, Microctis Folium, Crataegi Fructus, Cassiae Semen, Pogostemonis Herba, etc. IM T: 3.41 ± 2.56 years C: 4.02 ± 2.73 years 120 (60, 60) 67, 53 T: 34.61 ± 12.47 C: 36.37 ± 10.25 12 Niu, 2016 [ 48 ] Shugan Jianpi Huatan decoction Codonopsis Radix, Atractylodis Macrocephalae Rhizoma, Poria, Alismatis Rhizoma, Coicis Semen, Artemisia Scopariae Herba, Radix Bupl...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… IM T: 1–12 years C: 1–13 year 140 (70, 70) 83, 57 T: 42.9 ± 5.3 C: 43.2 ± 5.7 8 Jiang et al, 2017 [ 41 ] Dahuang Lidan capsule Rhei Radix Et Rhizoma, Phyllanthi Fructus and Radix Gymnadeniae IM N/A 144 (72, 72) 104, 40 T: 43.0 ± 0.03 C: 43.4 ± 7.60 9 Yang et al, 2017 [ 53 ] Cigu Xiaozhi capsule Cremastrae Pseudobulbus, Alismatis Rhizoma, Crataegi Fructus, Salviae Miltiorrhizae Radix Et Rhizoma, Radix Bupleuri, Pinelliae Rhizoma Praeparatum, Cassiae Semen, etc. WM N/A 87 (43, 44) 50, 37 T: 49.02 ± 11.19 C: 50.63 ± 10.97 10 Jeong et al, 2017 [ 28 ] HL tablet Extract of Magnolia officinalis WM N/A 72 (22, 23, 23)* 54, 18 H: 39.1 ± 9.5 L: 45.5 ± 11.5 C: 42.7 ± 11.2 11 Sun et al, 2017 [ 68 ] Jianpi Qushi prescription Codonopsis Radix, Poria, Microctis Folium, Microctis Folium, Crataegi Fructus, Cassiae Semen, Pogostemonis Herba, etc. IM T: 3.41 ± 2.56 years C: 4.02 ± 2.73 years 120 (60, 60) 67, 53 T: 34.61 ± 12.47 C: 36.37 ± 10.25 12 Niu, 2016 [ 48 ] Shugan Jianpi Huatan decoction Codonopsis Radix, Atractylodis Macrocephalae Rhizoma, Poria, Alismatis Rhizoma, Coicis Semen, Artemisia Scopariae Herba, Radix Bupl...…”
Section: Resultsmentioning
confidence: 99%
“… Liver function Out of the 47 trials which tested the related biochemical response measures of liver function, 19 trials reported the changes in AST, ALT, GGT, 17 trials reported ALT and AST change, 4 trials reported ALT, AST, ALP and GGT change, and 4 trials also reported TB. One trial also reported the MRS and free fatty acid to assess of hepatic fat content [ 28 ]. Blood sugar Out of the 12 trials that reported the results of the related biochemical response measures of blood sugar, 7 trials reported FBG, FNIs, HOMA-IR results, and 1 trial [ 42 ] reported the Hb1A results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations